Internalisasi Nilai-Nilai Pendidikan Islam Pada Anak Usia Dini - Lastri Khasanah (STAI Sufyan Tsauri Majenang, 2021)
Early childhood is a time of character and personality building. It is very important to instill religious values when children are easy to accept or respond to something through expressions, speech, five senses, and even experiences. The development of religion in early childhood occurs through life experiences that are acquired since childhood both in the family, in the school environment, and in the community. Children begin to know God through the words and actions of those around them. Important Islamic values are instilled in early childhood in the form of faith values, worship values, and moral values. While the methods can be applied in the internalization of Islamic values include exemplary methods, habituation methods, story methods, and field trips.